KONTRIBUSI KESIAPAN BELAJAR TERHADAP HASIL BELAJAR SISWA KELAS X MATA PELAJARAN GAMBAR BANGUNAN JURUSAN TEKNIK BANGUNAN SMK NEGERI 5 PADANG - 722-728 , Kiki Eka Putra (CIVED, 2015)
ABSTRACT              This research aims to determine how prepared students learn subjects Image Building at SMK 5 Padang. Total population is all students of class X TGB1 and TGB2 at SMK 5 Padang, as many as 39 people / students. The samples in this research using total sampling. Collecting data in this research using a questionnaire. Data were analyzed by using descriptive statistical analysis using SPSS 17.00. From the analysis of the data shows that there is a contribution to the readiness to learn of the results of class X student subjects Image Building SMK N 5 Padang at 17.31 % , so the higher the students' readiness, the higher student learning outcomes.   Keywords: Kontribusi, Kesiapan dan Hasil Belajar.